The Analytical Thinking Ability of Prospective Science Teachers: An Overview of Study Programs and Gender - Lukman Nasution; Baiq Nurhidayati Kartiwi Putri Rinjani; Hunaepi Hunaepi; Taufik Samsuri (Postgraduate, University of Mataram, 2023)
The study aimed to describe the analytical thinking skills of science teacher candidates based on the study program and gender. This research is a descriptive quantitative study with a sample of 80 students, 20 boys and 60 girls from the Biology Education Study Program (38 students), Physics Education (13 students), and Chemistry Education (29 students). The instrument used is descriptive subjective test questions adapted to three indicators of analytical thinking skills, namely differentiating, organizing, and attributing. Analyzed descriptively and statistically. The instrument used has been declared valid with Cronbach's Alpha reliability of 0.77. The results of the study show that overall, students' analytical thinking skills are quite analytical. However, there are differences in the ability to think analytically based on the study program. In addition, there is also a difference in the ability to think analytically between female and male students, although the difference is not too significant, namely only 4.63%. Based on these findings, it is necessary to make efforts to improve the analytical thinking skills of prospective science teacher students through the development of learning programs that focus more on developing analytical thinking skills.